On some computations of refined Donaldson-Thomas invariants - Cazzaniga, A (2015)
Donaldson and Thomas defined Donaldson-Thomas (DT) invariants for moduli spaces of sheaves on proper Calabi-Yau threefolds in [DT,T]. The definition has been extended to more general moduli spaces of objects in 3-Calabi-Yau categories, and in the last few years there has been an increasing interest in studying refinements of DT invariants. This thesis is devoted to the computation of the generating series of refined DT invariants in some geometric examples.